Quest for answers: lessons from Geneva - Raj, Ankit (Research and Humanities in Medical Education, 2020)
Equity and global health are two sides of the same coin. Many do not know how to flip that coin. In this perspective piece, I discuss global health from the two ends of the same spectrum. As a kid growing up in the poorest state of India and directly facing the consequences of disastrous public health and hygiene conditions; and then as a young medical student participating in an assembly of the highest decision making body of health - the World Health Assembly in Geneva - and subsequently realizing the irony and hypocrisy that comes with it. This is a reflective piece that tries to simplify the highly complex issues of global health and equity and, towards the end, leaves the interpretation open to readers.